Analisis Literasi Keuangan dan Digital Skill terhadap Kinerja SDM Perajin Ketak Berbasis Keunggulan Bersaing - Detty Agustin Riscal; Nur Fitrianingsi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Ketak handicraft is one of the leading creative industry sectors in West Nusa Tenggara Province that contributes to the local economy, yet it still faces challenges related to limited managerial capacity and technological adaptation of craftsmen. This study aims to analyze the effect of financial literacy and digital skills on the human resource performance of ketak craftsmen, with competitive advantage as a mediating variable. This research employs an explanatory quantitative approach by collecting data through questionnaires from 50 ketak craftsmen in Beleka Village, Central Lombok Regency, using purposive sampling. Data analysis was conducted using Partial Least Square (PLS-SEM) with SmartPLS 4.0. The results indicate that financial literacy and digital skills have a positive and significant effect on HR performance. Furthermore, competitive advantage significantly mediates the relationship between financial literacy, digital skills, and HR performance. These findings highlight that improving craftsmen’s performance depends not only on technical production skills but also on financial management capabilities and digital technology utilization to create market competitiveness. The limitation of this study lies in the limited sample size and its focus only on ketak artisans in Beleka Village. The recommendation of this study is the need for financial literacy and digital skills training for ketak artisans to improve competitiveness and human resource performance.